The morphology and histology of the male genital system of the squid Loligo reynaudii (d'Orbigny) - Badenhorst, J. H.(Johannes Hendrik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- Universiteit van Stellenbosch, 1973.